High adult sex ratios and risky sexual behaviors: a systematic review. - Cedric H Bien; Yong Cai; Michael E Emch; William Parish; Joseph D Tucker (PLoS ONE)
Background Thirty-four countries worldwide have abnormally high sex ratios (>102 men per 100 women), resulting in over 100 million missing women. Widespread sex selective abortion, neglect of young girls leading to premature mortality, and gendered migration have contributed to these persistent and increasing distortions. Abnormally high adult sex ratios in communities may drive sexually transmitted disease (STD) spread where women are missing and men cannot find stable partners. We systematically reviewed evidence on the association between high community sex ratios and individual sexual behaviors. Methods and findings Seven databases (PubMed, Web of Science, Embase, Scopus, The Cochrane Database of Systematic Reviews, Sociological Abstracts, and PopLINE) were searched without restrictions on time or location. We followed PRISMA guidelines and evaluated quality according to STROBE criteria. 1093 citations were identified and six studies describing 57,054 individuals were included for review. All six studies showed an association between high community sex ratios and individual sexual risk behaviors. In high sex ratio communities, women were more likely to have multiple sex partners and men were more likely to delay first sexual intercourse and purchase sex. Only two studies included STD outcomes. Conclusions High community sex ratios were associated with increased individual sexual risk behavior among both men and women. However, none of the studies examined unprotected sex or appropriately adjusted for gendered migration. Further studies are needed to understand the effect of community sex ratios on sexual health and to inform comprehensive STD control interventions.